(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Automotiveindustry has hundreds of suppliers and thousands of spare parts units. Due toglobalization, the automotive supply chain has been undergoing tremendouschanges and the industry has been exploring innovative methods to reduceoperating cost, lead time and inventory to sustain their growth in the market.With the expansion of sourcing partners, streamlining customer requirements,inventory management, accurate forecasting, better suppliers‘ relation,coordination and co-operation across supply chain, better visibility andcontrol over the process and reduction of lead time is being achieved by theorganizations. The Indian auto industry is small in size, compared to the worldmarkets ( 6.73 billion compared to a world market of 737 billion) but hasexperienced a growth rate of 20-25% in the past few years. Despite higher rawmaterial costs, higher energy costs and poorer infrastructure in India,multinational OEMs that have entered the Indian market have managed to producecars that have high local content and are sold at competitive retail prices,largely owing to efficient supply chain. The last few years have seen greaterintegration of the Indian automobile industry with its global counterparts.Most significant challenge identified by automotive Players in India is‗integrating the entire supply chain‘ and managing it as a single integratedentity. Managing inbound logistics remains another key concern for OEMs as wellas auto component players, driven more by challenges related to reliability ofdata, lead time and absence of quality logistics players on the upstream side.The present paper attempts to capture the innovative supply chain practices inIndian Automobile Industry, identify key challenges involved in integration andimplementation of supply chain, and suggests strategies to overcome thechallenges for optimum leverage.